2008
DOI: 10.1073/pnas.0711463105
|View full text |Cite
|
Sign up to set email alerts
|

The endocochlear potential depends on two K + diffusion potentials and an electrical barrier in the stria vascularis of the inner ear

Abstract: hearing ͉ ion transport ͉ potassium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
249
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(283 citation statements)
references
References 44 publications
(57 reference statements)
28
249
2
1
Order By: Relevance
“…The location of these proteins along the membranes of the different cells of the adult stria vascularis is depicted in Figure 1(B). Disrupting the function of any of these proteins (including connexin proteins) in the stria vascularis or at other locations in the cochlea where they are thought to be involved in K + homeostasis results in immediate SNHL (Cohen‐Salmon et al, 2002; Teubner et al, 2003; Nin et al, 2008). In many cases of both syndromic (as mentioned above) and nonsyndromic SNHL, the endocochlear potential is likely to be affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location of these proteins along the membranes of the different cells of the adult stria vascularis is depicted in Figure 1(B). Disrupting the function of any of these proteins (including connexin proteins) in the stria vascularis or at other locations in the cochlea where they are thought to be involved in K + homeostasis results in immediate SNHL (Cohen‐Salmon et al, 2002; Teubner et al, 2003; Nin et al, 2008). In many cases of both syndromic (as mentioned above) and nonsyndromic SNHL, the endocochlear potential is likely to be affected.…”
Section: Discussionmentioning
confidence: 99%
“…On the basolateral membranes of the marginal cells, K + uptake from the intrastrial space (the narrow fluid‐containing space between the marginal cells and the melanocytes) is mediated by the sodium‐potassium pump Na + /K + ‐ATPase (Schulte and Adams, 1989) and the Na + 2Cl ‐ K + cotransporter. Na + /K + ‐ATPase is known to be expressed in the adult human stria vascularis (Weber et al, 2001) and inhibition of Na + /K + ‐ATPase directly suppresses the endocochlear potential in guinea pigs (Kuijpers and Bonting, 1970; Nin et al, 2008). We found first expression of KCNQ1 on the luminal membranes of the marginal cells at W16.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This maintenance ensures the longevity of sensory hair cells and the generation of the endocochlear potential. The ion transporting mechanisms that regulate these concentrations have been characterized in a number of cochlear tissues, leading to widely held hypotheses of K + "recirculation" and "spatial buffering" (Forge et al 2003a;Hibino and Kurachi 2006;Kikuchi et al 2000;Kikuchi et al 1995;Nickel and Forge 2008;Nin et al 2008;Spicer and Schulte 1996;Takeuchi et al 2000;Wangemann 2006;Weber et al 2001;. In common with these mechanisms studied in the CNS and retina (Kofuji and Newman 2004), cochlear K + recirculation and spatial buffering both rely on gap junctional coupling throughout the epithelial cell network, and the ability of cells at the edges of the network to secrete K + .…”
Section: Discussionmentioning
confidence: 99%
“…The ionic composition of endolymph and the magnitude of the endocochlear potential (EP) in scala media are both regulated by stria vascularis (Nin et al 2008;Souter and Forge 1998). Experimental evidence from in vivo studies has suggested that K + in endolymph is sourced from perilymph, rather than from the blood supply (Wada et al 1979).…”
Section: Introductionmentioning
confidence: 99%